PERAN NOTARIS DALAM PELAKSANAAN PERJANJIAN BANGUN BAGI ANTARA ORANG-PERORANGAN DI KOTA JAMBI - Triamy Rostarum (Universitas Batanghari Jambi, 2018)
The form of conveyance are not only through legal act sales and purchase agreement. Land owners who want to build a building in their land,but do not have the funds (capital) can do the deed of the build and sharing Agreement. Build and sharing agreement is a legal agreement between a person who was land owner and another party(second party) who is given the right to build on the land, on condition that the profits are divided into two: for the land owner and the developer. Build and sharing agreement can be made by a notarial deed as an autenthic deeds. Notary as an official appointed by the State authorities in making the deed of build and sharing agreement. Notary is the instrumental intranslating carefully and clearly explained the intent of the parties, thus achieved an agreement between the parties.The role of notary is more than that set in the Act, notary act as mediator in differences of views against something in a legal agreement between two parties. Also, notary must explain the risks and constraints that may be encountered later in the implementation of the build and sharing agreement and mediate in seeking the prevention and solution to these constraints. The constraints faced in the implementation of build and sharing agreement are construction delay; negligence committed by second party and occurred problems in land ownership.Keywords: Build and sharing Agreement, the role of the notary.